Perancangan Sistem Pendukung Keputusan Instruktur Terbaik Berdasarkan Kinerja Dengan Metode Analytical Hierarchy Process (Ahp) - Intan Mutia; Luh Putu Widya Adnyani (Faktor Exacta, 2018)
Abstract. Instructor by large Indonesian dictionary means the person in charge to teach something and provide training and guidance.  The performance assessment Instructors can boost the quality of teaching and increase the motivation and professionalism of the instructors in performing the tasks. Chief Instructor establish criteria or requirements to determine the best fit instructor performanceThe criteria include: Presence / attendance, discipline of rules, responsibility and productivity, social interaction, motivation in self-development, responsiveness and initiative, communication, teamwork, friendly and polite, cleanliness and tidiness of class. Determination of the instructor's performance is done by using Analytical Hierarchy Process (AHP) method which then processed with Criterium Decision Plus (CDP) software. The results showed that Teacher C was chosen as the best structure among the three other teachers, with a score of 0.351.Keywords: Analytical Hierarchy Process, Instructor, Performance, System Decision